Understanding the Democratic Republic of the Congo’s agricultural paradox: Based on the eAtlas data platform - Marivoet, Wim; Ulimwengu, John M.; El Vilaly, Mohamed Abd Salam (International Food Policy Research Institute, 2018)
The huge agricultural potential of the Democratic Republic of the Congo (DRC) is well Documented. The country is endowed with well over two million square kilometers (km2) of land, 800 thousand of which is arable, yet only 10 percent is currently under cultivation. DRC also has favorable climatic and ecological conditions, allowing several harvests of numerous crops per year. Nevertheless, few studies have looked at the country’s spatial heterogeneity in terms of economic activity, public goods, or the livelihood strategies of smallholder farmers. As a result, policymakers have little evidence to guide their decisions in planning and implementing interventions to improve the nation’s food and nutrition security status. To fill in this knowledge deficit, the Regional Strategic Analysis and Knowledge Support System (ReSAKSS), which is facilitated by the International Food Policy Research Institute (IFPRI), provides knowledge products and analytical tools in support of African countries. Among the tools developed, country eAtlas—which is freely available online (http://eatlas. resakss.org/)—is a highly interactive, geographic information systems–based mapping tool designed to provide policymakers and analysts with access to high-quality, highly disaggregated data on agricultural, socioeconomic, and biophysical indicators.